Cuttability and drillability studies towards predicting performance of mechanical miners excavating in hyperbaric conditions of deep seafloor mining. (June 2020) - Balci, Cemal; Copur, Hanifi; Bilgin, Nuh; Ozdemir, Levent; Jones, Glen R.
Abstract: The research program outlined in this paper starts with the assumption that if there is a significant relationship between drilling and cutting specific energies in atmospheric conditions, there would also be a significant relationship between these variables in hyperbaric conditions. Five "model rock samples" having uniaxial compressive strength varying from 9 to 160 MPa were subjected to full-scale laboratory drilling tests with polycrystalline diamond compact (PDC) drill bits and a core drill, as well as laboratory full- and small-scale linear cutting tests with a conical and chisel cutter in atmospheric conditions. As a result, significant correlations between drilling and cutting specific energies were found for atmospheric conditions of laboratory. PDC drill bits and core drill bit used in laboratory tests were also used in the subsea drilling operations under hyperbaric conditions in Bismarck Sea. The conical cutter used in the laboratory tests are intended to be used on mechanical miners for subsea metal production. Core samples taken from Bismarck undersea mineral deposits were also subjected to physical and mechanical property tests in the deck and separately in the laboratories of Istanbul Technical University; and small-scale linear cutting tests were also applied in the university. Significant correlations were also found between the results of small- and full-scale cutting test. It is concluded that the capabilities of in-situ measurements will permit to detect some physical and mechanical properties of undersea mineral deposits. These properties interpreted with laboratory drilling and cutting tests would serve a basis to predict performance of mechanical miners to be used in hyperbaric conditions.